Beyond Tech-Fluent Generations: Investigating Cross-Generational Technology Adoption Patterns in Collaborative Online Learning Spaces - Akhter, Shamim; Dev Prasad P, Rabindra; Tan, Mengqiu; Iftikhar, Sehrish (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study challenges the prevailing digital native’s paradigm by examining technology adoption patterns across different generational cohorts in collaborative online learning environments. It investigates how generational differences influence technology acceptance, usage behaviors, and learning outcomes in digital educational spaces. A mixed-methods approach was employed, combining quantitative surveys (n = 847) and qualitative interviews (n = 32) across four generational cohorts: Generation Z (born 1997–2012), Millennials (1981–1996), Generation X (1965–1980), and Baby Boomers (1946–1964). The study utilized the extended technology acceptance model (TAM2) framework, incorporating social influence and cognitive instrumental processes. Findings reveal significant variations in technology adoption patterns that transcend traditional generational assumptions. While Generation Z demonstrated higher initial technology acceptance rates (M = 4.23, SD = 0.87), Generation X showed superior sustained engagement in collaborative learning activities (M = 4.45, SD = 0.76). Baby Boomers exhibited unexpected adaptability when provided with appropriate scaffolding and support mechanisms. The digital natives concept oversimplifies technology adoption behaviors. Crossgenerational collaboration in online learning spaces benefits from differentiated instructional design approaches that acknowledge varying technological competencies while leveraging the unique strengths of each generational cohort.